PENGGUNAAN DEIKSIS PERSONA DALAM SOAL CHOUKAI NIHONGO NOURYOKU SHIKEN LEVEL N3 - Nurrachman, Diana; Aibonotika, Arza; Budiani, Dini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this research is to find out the usage of first deiksis persona, second deiksis persona, and third deiksis persona in the questions of choukai JLPT N3. The method used was descriptive qualitative, while for data collection technique used waslistening and note-taking techniques. The analysis of deiksis persona form used pragmatics theory of deiksis persona by Levinson (1983). The results of this research show that in the questions of choukai JLPT N3 found three types of deiksis persona on pronomina persona with each type of deiksis persona is divided into two forms namely singular and plural. The first deiksis persona is singular and plural, the second deiksis persona is singular, and the third deiksis persona is singular. KeyWords: Pragmatics, Deiksis Persona, Choukai JLPT N3, Japanese Language